Evaluation of Genetic Diversity of Papaver bractaetum Lindl. Populations in Alborz Mountain Using SCoT Molecular Markers - javad shaghaghi; alaeddin kordenaeej; ardeshir qaderi (Institue of Medicinal Plants, ACECR, 2019)
Background: Iranin poppy (Papaver bracteatum Lindl.) belongs to Papaveraceae family which has important alkaloids such as thebain. Objective: Investigation of genetic diversity and population structure of Iranian poppy populations from Alborz Mountains. Methods: Total DNA from 36 genotypes (12 individuals from each population) were extracted by doyle method. Thebaine of capsules were assayed by High performance liquid chromatography (HPLC) against standard curve of thebaine. Results: The 12 primers from 26applied SCoT primers amplified 181 scorable bands. Polymorphism Information Contents (PIC) index ranged from 0.233 to 0.335 with 0.289 mean. Resolving Power (RP) index ranged from 2.61 to 6.5. based on AMOVA the variance of within and among population were 57% and 43% respectively. Unweighted pair group method with arithmetic mean (UPGMA) based clustering grouped 36 genotypes into three main groups that was supported by principal coordinate analyses (PCoA). The highest (0.86) and lowest (0.76) similarity were between Polur, Siahbisheh and Taham, Siahbisheh populations respectively. Also, thebaine content was differences between populations. The maximum and minimum thebaine content was obtained in Polur and Taham population respectively. Conclusion: The results showed that the SCoT markers can separate the Iranian poppy population and it's an efficient tool for study of genetic diversity and population structure. Also results clarified considerable genetic diversity among P. bracteatum population in Alboraz mountains. Based on results of phytochemical and genetic study, thebaine production in Iranian poppy is controled by genetic and environment factors.